2020
DOI: 10.1051/e3sconf/202018902026
|View full text |Cite
|
Sign up to set email alerts
|

Effection of cordycepin on Inhibition proliferation by activating autophagy in HepG2 cell

Abstract: Cordycepin, the main active component of Cordyceps militaris, possesses a variety of biological activities. This paper investigated the inhibition of cordycepin on liver tumors. HepG2 cells were treated with cordycepin. The inhibition rates of cell proliferation was detected by MTT, LC3 protein was detected by immunofluorescence method, autophagy was observed by transmission electron microscopy, autophagy related protein was detected by Western blot. The results showed that cordycepin significantly inhibited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Finally, autophagosomes are linked by adaptor proteins such as P62 to deliver aggregated proteins to lysosomes for degradation [ 28 ]. Normally, the autophagy is at a low level under physiological conditions [ 68 ]. In disease conditions especially in DM, a large number of abnormally folded proteins, impaired mitochondria, and free radicals caused to proteins and organelle damaged and produce toxic effects on cell [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, autophagosomes are linked by adaptor proteins such as P62 to deliver aggregated proteins to lysosomes for degradation [ 28 ]. Normally, the autophagy is at a low level under physiological conditions [ 68 ]. In disease conditions especially in DM, a large number of abnormally folded proteins, impaired mitochondria, and free radicals caused to proteins and organelle damaged and produce toxic effects on cell [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, activation of autophagy is an acute response of damaged cells and helps to protecting cell [ 75 ]. There have many studies found that cordycepin could ameliorated the disease, especially in DM complications, via inducing autophagy both of in vitro and in vivo [ 10 , 22 , 43 , 68 ]. As previous described, cordycepin could inducing autophagy via AMPK phosphorylation [ 18 , 74 ].…”
Section: Discussionmentioning
confidence: 99%